The Effect of Social Media Marketing on Brand Image, Brand Trust, and Purchase Intention of Somethinc Skincare Products in Surabaya - Lena Ellitan; Laurencia Geraldine Dinda Harvina; Robertus Sigit Haribowo Lukito (Journal of Entrepreneurship and Business, 2022)
Pupose: This study aims to analyze the effect of social media marketing, brand image, and brand trust on the purchase intention of Somethinc skincare products in Surabaya. These days, the internet has been growing rapidly over time. In Indonesia, internet users increase from year to year. The internet can also be an essential tool for media promotion by using social media, which can effectively create a good brand image and brand trust that can be expected to foster purchase intentions for a product. Method: This study used a purposive sampling technique, with the number of samples being 160 respondents. The respondents' characteristics were social media users who had seen content on Somethinc social media, were domiciled in Surabaya, and aged more than 17 years old. The data used were primary data obtained by distributing questionnaires. The data analysis technique used was Structural Equation Modeling with SmartPLS software Result: The results of the study prove that Social Media Marketing has a significant effect on Brand Image, Social Media Marketing has a significant effect on Brand Trust, Brand Image has a significant effect on Purchase Intention, Trust has a significant effect on Purchase Intention, Social Media Marketing has an effect which has a significant effect on Purchase Intention through Brand Image, and Social Media Marketing has a significant effect on Purchase Intention through Brand Trust